Comprehensive identification and structural characterization of target components from Gelsemium elegans by high‐performance liquid chromatography coupled with quadrupole time‐of‐flight mass spectrometry based on accurate mass databases combined with MS/MS spectra. (8th June 2017) - Liu, Yan‐Chun; Xiao, Sa; Yang, Kun; Ling, Li; Sun, Zhi‐Liang; Liu, Zhao‐Ying
Abstract : This study reports an applicable analytical strategy of comprehensive identification and structure characterization of target components from Gelsemium elegans by using high‐performance liquid chromatography quadrupole time‐of‐flight mass spectrometry (LC‐QqTOF MS) based on the use of accurate mass databases combined with MS/MS spectra. The databases created included accurate masses and elemental compositions of 204 components from Gelsemium and their structural data. The accurate MS and MS/MS spectra were acquired through data‐dependent auto MS/MS mode followed by an extraction of the potential compounds from the LC‐QqTOF MS raw data of the sample. The same was matched using the databases to search for targeted components in the sample. The structures for detected components were tentatively characterized by manually interpreting the accurate MS/MS spectra for the first time. A total of 57 components have been successfully detected and structurally characterized from the crude extracts of G. elegans, but has failed to differentiate some isomers. This analytical strategy is generic and efficient, avoids isolation and purification procedures, enables a comprehensive structure characterization of target components of Gelsemium and would be widely applicable for complicated mixtures that are derived from Gelsemium preparations. Copyright © 2017 John Wiley & Sons, Ltd.